Estudos de validade da escala de dependência alcoólica do millon clinical multiaxial inventory iii para o Brasil - Sousa, Heloisa Karmelina Carvalho de (2011)
This study has as main objectives to translate and to adapt the MCMI-III to brazilian Portuguese, as well as investigate and analyze the involved modifications in the Alcohol Dependence Scale concerning to the results obtained on the validity and on the process of adaptation to Brazil. The inventory was translated and, posteriorly, applied on people with different reading levels to certify that the items are understandable to public in general, from diverse places of the country, divided into clinical and non-clinical groups. Were evaluated 2855 subjects between the ages of 18 and 85 years old, male and female, resident and dwellers of Brazilian cities. The application methods were face-to-face and computerized. Results showed that the clinical group presented significant differences between the means in comparison to the non-clinical group. Through the application of the General Health Questionnaire were developed studies related to the achievement of convergent validity and its results pointed to the relation between the instrument scores and the MCMI-III. The Alcohol Dependence Scale analysis indicated that people who reported abusive use of alcohol had highest scores, indicating adequacy of the instrument on identifying manifestation of disorders and syndromes. Nevertheless, further studies are necessary to the establishment of normative patterns to the Brazilian sample